Clinical outcomes of endoscopic submucosal dissection for superficial esophageal neoplasms: a multicenter retrospective cohort study - Tsujii, Yoshiki; Nishida, Tsutomu; Nishiyama, Osamu; Yamamoto, Katsumi; Kawai, Naoki; Yamaguchi, Shinjiro; Yamada, Takuya; Yoshio, Toshiyuki; Kitamura, Shinji; Nakamura, Takeshi; Nishihara, Akihiro; Ogiyama, Hideharu; Nakahara, Masanori; Komori, Masato; Kato, Motohiko; Hayashi, Yoshito; Shinzaki, Shinichiro; Iijima, Hideki; Michida, Tomoki; Tsujii, Masahiko; Takehara, Tetsuo (Endoscopy, 2015)
Background and study aims: The safety and efficacy of endoscopic submucosal dissection (ESD) for superficial esophageal neoplasms (SENs) have not been evaluated in a multicenter survey. The aim of this study was to investigate the clinical outcomes in a multicenter study that included municipal hospitals. Patients and methods: Of 312 consecutive patients with 373 esophageal lesions treated by ESD at 11 hospitals from May 2005 to December 2012, a total of 368 SENs in 307 patients were retrospectively analyzed. Results: The median tumor size was 18 mm (range 2 – 85 mm). The median procedure time was 90 minutes (range 12 – 450 minutes). The en bloc resection and complete resection rates were 96.7 % (95 % confidence interval [CI] 94.4 % – 98.1 %) and 84.5 % (95 %CI 80.5 % – 87.8 %), respectively. Perforation (including mediastinal emphysema), postoperative pneumonia, bleeding, and esophageal stricture, occurred in 5.2 % (95 %CI 3.3 % – 7.9 %), 1.6 % (95 %CI 0.7 % – 3.5 %), 0 %, and 7.1 % (95 %CI 4.9 % – 10.2 %) of patients, respectively. All of these complications were cured conservatively. No procedure-related mortality occurred. Early treatment periods (odds ratio [OR] = 4.04; P < 0.01) and low volume institutions (OR = 3.03; P  = 0.045) were significantly independent risk factors for perforation. The circumference of the lesion was significantly associated with postoperative stricture (OR = 32.3; P < 0.01). The procedure times significantly decreased in the later period of the study (P < 0.01). Follow-up data (median 35 months; range 4 – 98 months) showed significant differences in overall survival (P = 0.03) and recurrence-free survival (P < 0.01) rates between patients with curative and noncurative resections.Conclusions: Esophageal ESD has become feasible with acceptable complication risks and favorable long term outcomes.